Forced migration and mental health : rethinking the care of refugees and displaced persons - Ingleby, David (International and cultural psychology series, 2005)
The phenomenon of forced migration dates back to the beginning of human history. In our time, however, it has become one of the world's major problems. Since 1945 a virtual epidemic of armed conflict, both within and between nations, has created vast numbers of asylum seekers, refugees and displaced persons. This has led in turn to increasing involvement on the part of professional care workers and agencies, both governmental and non-governmental. In the last two decades, the provision of appropriate mental health care for the victims of organized violence has become a major focus of concern. That care should be provided is--fortunately--increasingly accepted: however, considerable controversy has arisen about the kind of care that is necessary. The assumptions and models which initially informed mental health care provision for displaced persons, refugees and asylum seekers have come under scrutiny. As professionals become better acquainted with the problems, alternative approaches are starting to come to the fore. This book aims to present a critical review of mental health care provisions for these groups of people and to review the controversies currently surrounding this topic. Part I discusses issues arising in humanitarian aid and reconstruction programs; Part II focuses on service provision in host countries. In both areas, we set out to highlight the controversies and new developments.